From identification to functional characterization of cyriotoxin‐1a, an antinociceptive toxin from the spider Cyriopagopus schioedtei. (9th April 2019) - Gonçalves, Tânia C.; Benoit, Evelyne; Kurz, Michael; Lucarain, Laetitia; Fouconnier, Sophie; Combemale, Stéphanie; Jaquillard, Lucie; Schombert, Brigitte; Chambard, Jean‐Marie; Boukaiba, Rachid; Hessler, Gerhard; Bohme, Andrees; et al.
Abstract : Background and Purpose: The NaV 1.7 channel is highly expressed in dorsal root ganglia of the sensory nervous system and plays a central role in the pain signalling process. We investigated a library prepared from original venoms of 117 different animals to identify new selective inhibitors of this target. Experimental Approach: We used high throughput screening of a large venom collection using automated patch‐clamp experiments on human voltage‐gated sodium channel subtypes and then in vitro and in vivo electrophysiological experiments to characterize the active peptides that have been purified, sequenced, and chemically synthesized. Analgesic effects were evaluated in vivo in mice models. Key Results: We identified cyriotoxin‐1a (CyrTx‐1a), a novel peptide isolated from Cyriopagopus schioedtei spider venom, as a candidate for further characterization. This 33 amino acids toxin belongs to the inhibitor cystine knot structural family and inhibits hNaV 1.1–1.3 and 1.6–1.7 channels in the low nanomolar range, compared to the micromolar range for hNaV 1.4–1.5 and 1.8 channels. CyrTx‐1a was 920 times more efficient at inhibiting tetrodotoxin (TTX)‐sensitive than TTX‐resistant sodium currents recorded from adult mouse dorsal root ganglia neurons and in vivo electrophysiological experiments showed that CyrTx‐1a was approximately 170 times less efficient than huwentoxin‐IV at altering mouse skeletal neuromuscular excitability properties. CyrTx‐1a exhibited an analgesic effect in mice by increasing reaction time in the hot‐plate assay. Conclusions and Implications: The pharmacological profile of CyrTx‐1a paves the way for further molecular engineering aimed to optimize the potential antinociceptive properties of this peptide.